Sounding John Thompson’s White Noise - Clarke, George Elliott (Studies in Canadian Literature, 2011)
John Thompson and Malcolm X may have more in common than coincidences in their respective biographical histories. Although generally overlooked as a political poet, Thompson, superb writer of the Tantramar, employs images of black and white, dark and light in his writings to engage with specific conceptions of race and imperialism – developed more explicitly in the theoretical work of Toni Morrison and Frantz Fanon – that informed the tumultuous political climate of his and X’s era. As a former student of psychology, the English-born, U.S.-educated Thompson would have been aware of the fundamental significance of blackness and whiteness in Western society, and many of his poems develop an idea of whiteness as a facade that works to obscure a primal or fundamental blackness. This exploration of the darker recesses of Thompson’s poetry draws him more clearly into the company of his primary influences, themselves all highly political writers: English-language poets Ezra Pound, William Butler Yeats, and Dylan Thomas; French poets Charles Baudelaire, Arthur Rimbaud, and René Char; and Québécois poets Roland Giguére and Paul-Marie Lapointe.